Students’ Perceptions of Grades and Grade Inflation in Counselor Training - Daniel A. DeCino; Phillip L. Waalkes; Steven Chesnut (Teaching and Supervision in Counseling, 2023)
Previous scholars have suggested grade inflation has been in higher education for decades, may devalue high grade point averages, and blur important differences between qualified and unqualified job candidates. In counselor training programs, grade inflation may cause students to overestimate their abilities to handle challenging real-world situations, impede faculty evaluation practices, and promote unfavorable student learning environments. In this exploratory study, we surveyed 240 counseling students on their perceptions of their grades and their peers’ grades before and during the COVID-19 pandemic. Our results suggest that students perceived their peers succeeded academically despite inappropriate and unethical behaviors, especially during the COVID-19 pandemic. Counselor educators should consider how grade inflation might impact student learning and training, and program alignment with CACREP standards.
Keywords: grade inflation; counselor training; instructional assessment; pedagogy; counselor education